2019
DOI: 10.1177/0886109919882320
|View full text |Cite
|
Sign up to set email alerts
|

Soft Sterilization: Long-Acting Reversible Contraceptives in the Carceral State

Abstract: In the United States, between 1907 and 1978, the proliferation of eugenic state practices routinely targeted institutionalized women with legalized involuntary sterilization. Sterilization laws and policies were a form of reproductive control, which predominantly impacted women from marginalized communities. After the implementation of federal regulations prohibiting involuntary sterilization practices, state agencies continued to engage in coercive sterilization under the guise of “voluntariness.” Using a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Historically, there has been an erasure of systematically minoritized women regarding sexual and reproductive health within policy, legislation, equitable research methods, and healthcare practices (Brown et al, 2021; Marchevsky, 2021). Women of color have practices such as forced (Brown et al, 2021; Marchevsky, 2021) or “soft” (Winters & McLaughlin, 2020) sterilization in the form of total hysterectomies or long-acting reversible contraceptives such as intrauterine devices imposed without full informed consent or participation. As such, the historical mistrust of researchers that often exists among underserved childbearing populations is not unfounded.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, there has been an erasure of systematically minoritized women regarding sexual and reproductive health within policy, legislation, equitable research methods, and healthcare practices (Brown et al, 2021; Marchevsky, 2021). Women of color have practices such as forced (Brown et al, 2021; Marchevsky, 2021) or “soft” (Winters & McLaughlin, 2020) sterilization in the form of total hysterectomies or long-acting reversible contraceptives such as intrauterine devices imposed without full informed consent or participation. As such, the historical mistrust of researchers that often exists among underserved childbearing populations is not unfounded.…”
Section: Resultsmentioning
confidence: 99%
“…The most common types of contraceptives among women in the United States are female sterilization (18.6%) and oral birth control pills (12.6%) as compared with LARCs (10.3%) (CDC, 2019). However, evidence has shown that justice-involved Black women are encouraged to use LARCs as a first-line recommendation instead of to other forms of contraception (Brandi & Fuentes, 2020; Holt et al, 2020; Winters & McLaughlin, 2020). In a 2019 review of policies related to contraception in jail and prison systems, only 65% of systems had written policies related to contraception with limited authorization in giving choice/options to justice-involved women related to their birth control (Cheedalla & Sufrin, 2021) which further supports our findings that reproductive autonomy is limited in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Continuation post‐incarceration requires access to reliable care in the community. If women decide to discontinue their method and restore fertility, without access to safe removal, they may be forced to continue contraception without consent (Winters & McLaughlin, 2020).…”
Section: Discussionmentioning
confidence: 99%